Role of Ketamine in the Treatment of Psychiatric Disorders - Sahar Derakhshanian; Maxine Zhou; Alexander Rath; Rachel Barlow; Sarah Bertrand; Caroline DeGraw; Christopher Lee; Jamal Hasoon; Alan D. Kaye (Health Psychology Research)
# Purpose of review